1998
DOI: 10.2508/chikusan.69.585
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Crude Fat Contents in Rib-Eye Muscle of Beef Using the Fat Area Ratio Calculated by Computer Image Analysis

Abstract: The purpose of this study was to examine the accuracy of estimation of crude fat contents in rib-eye muscle determined by chemical analysis from the fat area ratio calculated by computer image analysis (CIA). The materials used were 64 rib-eye images of 35 Japanese Black, 6 Angus and 23 F1 breed cattle. The fat area ratio was calculated using a software developed by the authors. The regression equation of the crude fat contents (Y) on the fat area ratio (X) calculated by CIA was Y=0.741 X-2.22 (r2=0.91, P<0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of image analysis to produce the official JMGA photographic standards and in direct carcase assessment has been reported by Kuchida et al (2006) and may provide a more sophisticated and objective tool for marbling classification (Kuchida et al 1997;Kuchida et al 1998;Kuchida et al 2000;Kuchida et al 2001). Konarska et al (2013) also reported a test procedure for image analysis of beef samples that had been first frozen and then thawed prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of image analysis to produce the official JMGA photographic standards and in direct carcase assessment has been reported by Kuchida et al (2006) and may provide a more sophisticated and objective tool for marbling classification (Kuchida et al 1997;Kuchida et al 1998;Kuchida et al 2000;Kuchida et al 2001). Konarska et al (2013) also reported a test procedure for image analysis of beef samples that had been first frozen and then thawed prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of breed groups were not included in the mathematical models, although several breed groups were used at Station A. Effects due to breed groups have been shown to be not significant (Kuchida et al, 1998). The GLM procedure of SAS (1989) was used for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This software draws contours of marbling particles for a specified area on the computer screen that displays the original color image of the ribeye area. The ratio of fat area (RFA) to area of ribeye muscle obtained with this program could be used as a linear covariate to predict crude fat percentage in ribeye muscle with high precision (r 2 = .91) and accuracy (error of prediction within ±3%; Kuchida et al, 1998). However, the image data in that study were taken by CCD camera at only one laboratory, and prediction error when using a traditional film camera, the type that is widely used to photograph meat, was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors used image analysis for intramuscular visible fat ratio evaluation in meat (Chandraratne et al, 2003;Kuchida, Konishi, Suzuki, & Miyoshi, 1998;Kuchida et al, 2000) and put into correlation the results with those obtained from chemical analysis, in order to find a new technique able, with some limits, to replace the latter which is expensive and long time taking. The correlations obtained were very high as fat distribution was probably very uniform.…”
Section: Visible Fat Area Ratiomentioning
confidence: 99%